The Garment Industry in Bangladesh, Corporate Social Responsibility of Multinational Corporations, and The Impact of COVID-19 - Reza, Ninia; Du Plessis, Jean Jacques (Asian journal of law and society, 2022)
This article investigates the Bangladeshi garment industry that supplies ready-made garments for global brands and the corporate social responsibilities (CSRs) of the brands/multinational corporations (MNCs) towards their supply chains. Although outsourcing and global trade have boosted the living standards of many people in the Bangladeshi garment industry, there are some significant concerns regarding the working conditions and treatment of workers in these supply chains. This, in turn, cannot, and should not, be detached from the legal relationship between the Bangladeshi supply chains and the MNCs contracting with them. This article examines the impact of COVID-19, which has exposed the fragility and the pre-existing flaws in the relationship between the MNCs and their suppliers more clearly than at any other time in history. There is a huge governance gap between MNCs and supply chains that needs to be addressed urgently. This article assesses the legality of the cancellation of orders by the brands that invoked the force majeure clause. In doing so, this paper briefly deals with the responses of three American retail companies, namely Sears, Kohl’s, and the Arcadia Group, in the wake of the COVID-19 pandemic. It illustrates that the power asymmetry between the MNCs and their suppliers has put the supply chains in an unreasonably disadvantageous position, creating unfair and even unconscionable conduct by several MNCs. This article also looks at solutions for the existing problems, focusing, inter alia, on non-financial reporting requirements in the US and the EU to implement CSR in supply chains. However, disappointingly, the authors had to conclude that MNCs typically have the propensity to disregard CSR, whenever it is convenient for them and use CSR for mere “greenwashing” purposes for their strategic benefit only. It is a problem that requires constant attention and continuing research to find long-term solutions. The article employs doctrinal methodology and, by conducting a meta-analysis of literature and case-studies, it provides a comprehensive understanding of how the industry works.